Effect of Profitability and Leverage on Firm Value with Dividend Policy as an Intervering Variable in LQ45 Companies on the IDX - Manisah; Andriyani, Ima; Oktarina, Linda (Neo Journal of economy and social humanities, 2023)
This study attempts to determine and demonstrate the direct and indirect effects of profitability and leverage on firm value in LQ45 businesses listed on the Indonesia Stock Exchange (IDX) over the 2018–2022 period, with dividend policy serving as an intervening variable. The LQ45 index serves as the study's population. Only 45 listed firms make up the LQ45 index. Purposive sampling, which selects the sample based on certain criteria, was used to conduct the sampling for this study. 11 companies were chosen as samples for this study based on preset criteria, making a total of 55 research data from 11 companies multiplied by 5 years of observation. The views used in this study's data analysis were 12 programs. The study's findings show that the dividend policy is influenced by the profitability variable (ROE) (DPR). Influence of Leverage Variable (DER) on Dividend Policy (DPR). ROE, a profitability indicator, influences firm value (PBV). Firm Value is impacted by Leverage Variable (DER) (PBV). Firm Value is impacted by the Dividend Policy Variable (DPR) (PBV). With a probability value of 0.0100 0.05, the interaction between dividend policy (DPR) and profitability (ROE) indicates that dividend policy (DPR) can mitigate the impact of profitability (ROE) on firm value (PBV). With a probability value between Dividend Policy (DPR) and Leverage (DER) of 0.0163 0.05, Dividend Policy (DPR) is able to attenuate the impact of Leverage (DER) on Firm Value (PBV). The R-squared value is 0.3736, or 37.36%, according to the findings of the coefficient of determination test (R2 test). The company value (PBV) of 37.36%, which is the dependent variable, may be explained or described by the independent variables of profitability (ROE), leverage (DER), and dividend policy (DPR), according to the findings of the coefficient of determination test (R2 test). In addition, other factors not considered in this study account for or describe 62.64% of the data.